Dynamic carbon dioxide adsorption column studies using bentonite modified with amine-functionalized pectin - Jovellana, John Andrew Kane P.
Increasing carbon dioxide (CO2) levels in the atmosphere caused by excessive greenhouse gas emissions is strongly associated to global warming and climate change. This study aims to prove the feasibility of using pectin as the backbone for amine functionalization with application as coating on bentonite for carbon dioxide capture. Characterization of the aminating solutions using Fourier Transform Infrared (FTIR) spectroscopy showed successful grafting of the aminating agent triethylenetetramine (TETA) to the pectin chains. Parametric studies probing the effect of bed mass, adsorption temperature, and influent gas flow rate on dynamic adsorption of pure CO2 were performed to determine the conditions of 10 g of adsorbent, 30°C, and 200 mL/min gas flow rate, respectively, for maximum adsorption capacities. Kinetic modeling of the adsorption behavior using pseudo-first order, pseudo-second order, Avrami fractional, modified Avrami fractional, Elovich, and intraparticle diffusion models were performed, with the modified Avrami fractional model providing the best fit. It has been reported for the first time that the polysaccharide pectin can be aminated for CO2 capture upon being coated on porous substrates such as bentonite. The adsorption capacity at 5% breakthrough of the bentonite coated with the TETA-modified pectin shown a maximum of 5.58 mmol CO2/g adsorbent, and a predicted equilibrium adsorption capacity of 12.24 mmol CO2/g adsorbent using the modified Avrami fractional kinetic model. It is recommended for further study to synthesize substrates with higher surface area, and optimize the formulations of the pectin modification, and characterize the pore structure of the adsorbents.